What keeps the market ticking? The role of third‐party audiences and cognitive embeddedness in shaping competitive dynamics in luxury watchmaking - Claes, Kim; Godart, Frédéric (Strategic Management Journal, 2025)
Abstract Research Summary Competitive dynamics between firms and buyers are shaped by mutually understood conceptual systems that enable market interactions. Third‐party audiences, such as the media, play a crucial role in shaping market structure and evolution by facilitating the development of these conceptual systems. Although they do not directly engage in contractual bargaining, third‐party audiences stabilize perceptions and facilitate market interactions by cognitively embedding competitive dynamics. Our study examines the coreness of firms within the semantic network of firm names as relayed by the media. We find that higher coreness positively impacts auction prices. This effect is moderated by firm visibility and the tone of media coverage. Our model is tested using a unique dataset from the luxury watchmaking industry. Managerial Summary We demonstrate that a firm's performance is shaped not only by how prominently or positively it is featured in the media, but also by the relational context in which it is mentioned. Firms that are frequently mentioned alongside other key industry players are perceived to be the core of the industry, leading to higher auction prices for their products. The effect is strengthened when a firm enjoys frequent and positive media coverage. For managers, our findings underscore the importance of understanding how and why the media associates their brand with others, as this can enhance its value in secondary markets, and thus potentially boost value capture in primary markets. Our analysis explores the luxury watchmaking industry, a setting that is rarely studied.